Localización industrial en el medio rural de Aragón. Aproximación a su correlación con las empresas de transporte regular y de mercancías - Garrido Palacios, José (Geographicalia, 2017)
This work estudies the industrial location in the rural areas in Aragón and the correlation with the transport passenger companies and the freight transport agencies.